DIAGNOSTIC ACCURACY OF GASTROPANEL® FOR ATROPHIC GASTRITIS IN BRAZILIAN SUBJECTS AND THE EFFECT OF PROTON PUMP INHIBITORS - MATTAR,Rejane (2020)
ABSTRACT BACKGROUND: It has been proposed that the combination of gastrin-17 (G-17), pepsinogens I and II (PGI and PGII), and anti-Helicobacter pylori (H. pylori) antibodies (GastroPanel®, BIOHIT HealthCare, Helsinki, Finland) could serve as biomarkers of atrophic gastritis. OBJECTIVE: This study aimed to ensure the diagnostic accuracy of GastroPanel® and evaluate the effect of proton pump inhibitors (PPIs) on these biomarkers. METHODS: Dyspeptic patients who underwent gastrointestinal endoscopy were enrolled in the present study. Histological findings, which were the gold standard to stratify groups, were as follows: no atrophy (controls); antrum atrophy; corpus atrophy; multifocal atrophy; and neoplasia. G-17, PGI, PGII, and anti-H. pylori immunoglobulin (Ig)G antibodies were assayed using commercially available kits. The ratio of PGI/PGII was calculated. RESULTS: Among 308 patients, 159 (51.6%) were PPI users. The overall prevalence of atrophy was 43.8% (n=135). Ninety-two (29.9%) patients were H. pylori positive according to anti-H. pylori IgG levels. G-17 levels were not low in those with antrum atrophy but were high in those with corpus and multifocal atrophies. PGI levels were significantly lower in those with corpus and multifocal atrophies. The sensitivity of PGI <30 µg/L to detect corpus atrophy was 50% (95% CI 27.8-72.1%), with a specificity of 93.2% (95% CI 84.3-97.5%), a positive likelihood ratio of 7.4 (95% CI 2.9-19.2), and a negative likelihood ratio of 0.5 (95% CI 0.3-0.8). A small number of subjects (n=6) exhibited moderate to intense atrophy (4%), among whom 66.7% exhibited decreased PGI levels. PPI significantly increased the levels of G-17 and PGI, except in those with corpus and multifocal atrophies, in whom PGI levels were not increased by PPIs. CONCLUSION: GastroPanel® (Gastrin-17, PGI, and PGI/PGII ratio) did not demonstrate high sensitivity for detecting gastric atrophy.